Improving the Capacity of Posyandu Cadres in Flipchart and Leaflet-Assisted Education for Toodler Diarrhea Management - Mariyam; Vivi Yosafianti Pohan (Jurnal Pengabdian Masyarakat Lentora, 2026)
Toodler diarrhea remains a leadin cause of morbidity and mortality in low and middle income countries, with effectivee home management being crucial to prevent deats. The purpose of this community service activity is to improve the knowledge and skills of Posyandu cadres in providing education on handling toddler diarrhea using flipchart and leaflet assisted training. The activity was carried out from December 2025 to January 2026, involving a total population of 13 cadres at RW 27 Tlogosari Kulon. The intervention consisted of a 4 hour intensive workshop featuring lectures, demonstrations of Oral Rehydration Salt (ORS) preparation and role pay sessions using media. one supervised mentoring session during actual Posyandu activities to ensure the practical application of the visual aids. Knowledge wa measured using a validated 20 item pre and post test questionnaire, while skils were assesed using a standardized clinical checklist during demonstrations. The  results showed a significant increase in knowledge; initialy, 61.5% of cadres had poor knowledge, which improved to 100% in the good categorty post intervention.Furthermore, cadres demonstrated 100 % proficiency in using flipcharts and corectly preparing ORS solution. This program effectively empowers cadres as frontline educators in comunity based diarrhea management.